Pharmacoeconomic research of using aflibercept in patients with the wet age-related macular degeneration - S. V. Nedogoda; A. S. Salasyuk; E. V. Bobykin; I. N. Barykina; V. O. Smirnova; E. A. Popova (Российский офтальмологический журнал)
Purpose. To evaluate the economic and clinical results of the aflibercept and ranibizumab angiogenesis inhibitors in the treat-and-extend regimen in patients with the “wet” form of age-related macular degeneration (wAMD). Materials and methods. We analyzed cost minimization, impact on the budget and “missed opportunities” for the treatment of patients with wAMD using intravitreal injections (IVI) of aflibercept compared to ranibizumab in the “treat-and-extend” regimen (T & E). Costs were calculated with regard to the budget of the system of compulsory health insurance. To calculate the number of IVI, network meta-analysis data (P. Lanzetta, et al., 2019), including a matching-adjusted indirect comparison of aflibercept and ranibizumab in wAMD patients in the T & E regimen, were taken into account. The budget impact analysis involved a cohort of 1,000 wAMD patients. To assess the stability of the results, a one-factor multicomponent sensitivity analysis was used. Results. Network meta-analysis data showed that aflibercept and ranibizumab used in the T & E regimen revealed comparable changes in the maximum corrected visual acuity; however, the use of aflibercept required a significantly lower (by 6 procedures in two years) number of IVI compared to ranibizumab. Analysis of cost minimization showed that the use of aflibercept can reduce costs by 36 % in two years compared to ranibizumab in the T & E regimen. The use of aflibercept in the T & E regimen with wAMD will reduce the cost of compulsory medical insurance by 281 million rubles in two years of therapy per 1,000 patients. The analysis of “missed opportunities” showed that budget savings of the compulsory medical insurance as a result of transferring 1,000 patients from ranibizumab to aflibercept will allow an additional 563 patients to be treated in two years. A sensitivity analysis confirmed the robustness of the study results. Conclusion. Treating wAMD with aflibercept in the T & E regimen saves a significant part of health protection resources compared to using ranibizumab in the same regimen.